The process of contemporary gay identity development in China: The influence of internet use - Zhang, Aidi; Reynolds, Nancy R.; Huang, Chongmei; Tan, Simin; Yang, Guoli; Yan, Jin (Frontiers in Public Health, 2022)
Background Adolescence and emerging adulthood are critical periods for an individual's sexual identity development. The internet has become a primary avenue for gay identity exploration. The purpose of this study was to examine the role of the internet in Chinese young gay male's sexual identity development. Methods Qualitative interviews were conducted with 37 gay males aged 16 to 29. Data were analyzed using grounded theory methods. Results Three categories of identity development in relation to use of the internet were identified: (1) Gay identity confirming, which includes verifying same-sex attraction and connecting the attraction feeling to gay identity through consumption of pornography, Tanbi (boy's love) materials, and searching for information online. (2) Gay identity practicing, includes interacting with the gay community to gain understandings of gay subcultures and make close gay friends, engaging in same-sex sexual and romantic relationship development through online group and interpersonal interactions. The internet practice impact on an individual's cognition and behavior by presenting same-sex sexual contact is normal and common, facilitating longing for a romantic relationship, and facilitating relationship development; and (3) Gay identity coping, includes increasing self-acceptance of gay identity, gaining a sense of belonging in the gay community, increasing autonomy in sexual and romantic relationship development, and growing consideration of coming out to parents. Young gay males' coping efficacy was gained through the lessons learned from identity practice. Conclusion The findings indicate that an individual's internet practice facilitates gay identity confirmation, enriches identity practice, and promotes the transition from self-identification to identity disclosure and integration. Internet practice also threatens to young gay males' sexual risk behavior, emotional hurts from failed romantic relationships. Interventions including sexual identity education and healthy internet use strategies need to be developed tailored to the developmental characteristics.